Novel Robust Control Using a Fractional Adaptive PID Regulator for an unstable system - Abdelhakim Idir; Yassine Bensafia; Khatir Khettab; Muhammad Saeed Akhtar; Sarwat Zahra (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
Recent advances in fractional order calculus led to the improvement of control theory and resulted in potential use of fractional adaptive PID controller in advanced academic and industrial applications as compared to the conventional adaptive PID controller. Basically, a fractional order  adaptive PID  controller  is  an  improved version of classical  integer  order  adaptive PID  controller that outperformed  its classical  counterpart. In case of a closed loop system, a minute change would result in instability of the overall system. An efficient PID controller can be used to control the response of such system.  Among various parameters of an instable system, speed of the system is an important parameter to be controlled efficiently. The current research work presents the speed controlling mechanism for an uncertain instable system by using fractional order adaptive PID controller.To validate the arguments, effectiveness and robustness of the proposed fractional order adaptive PID controller have been studied in comparison to the classical adaptive PID controller using The Criterion of quadratic error. Simulation findings and comparisons demonstrated that the proposed controller has superior control performance and outstanding robustness in terms of percentage overshoot, settling time, rising time, and disturbance rejection.